Cultural competency training of GP Registrars-exploring the views of GP Supervisors - Watt, Kelly (Int J Equity Health, 2015)
INTRODUCTION: An equitable multicultural society requires General Practitioners (GPs) to be proficient in providing health care to patients from diverse backgrounds. This requires a certain set of attitudes, knowledge and skills known as cultural competence. While training in cultural competence is an important part of the Australian GP Registrar training curriculum, it is unclear who provides this training apart from in Aboriginal and Torres Strait Islander training posts. The majority of Australian GP Registrar training takes place in a workplace setting facilitated by the GP Supervisor. In view of the central role of GP Supervisors, their views on culturally competent practice, and their role in its development in Registrars, are important to ascertain. METHODS: We conducted 14 semi-structured interviews with GP Supervisors. These were audiotaped, transcribed verbatim and thematically analyzed using an iterative approach. RESULTS: The Supervisors interviewed frequently viewed cultural competence as adequately covered by using patient-centered approaches. The Supervisor role in promoting cultural competence of Registrars was affirmed, though training was noted to occur opportunistically and focused largely on patient-centered care rather than health disparities. CONCLUSION: Formal training for both Registrars and Supervisors may be beneficial not only to develop a deeper understanding of cultural competence and its relevance to practice but also to promote more consistency in training from Supervisors in the area, particularly with respect to self-reflection, non-conscious bias and utilizing appropriate cultural knowledge without stereotyping and assumption-making.